COMPONENTS OF A MODEL PERMANENT FILE. - Brison, Clifford S. (The Accounting Review, 1946)
This article focuses on components of a model permanent file. The components number fourteen, which fall under three main classifications, governing or fundamental documents, audit guides and synopsis or accounts. The whole of the permanent file should be treated as esoteric, thus providing one more instance of the mystery which should properly attach to any professional man performing before his laity. The seven year plan of audit, however, might well be marked "Top Secret-Not to Fall under Clients' Eyes." In case of accidents, it should not be sidescored for more than one year in advance, and this might well he done during the review of the current audit or during the now-busy season. Compared with the hard work represented by the current file of audit working papers, the compilation and bringing up to date of the permanent file will be found to be almost a pastime. The time spent on its initiation, however, will be found to pay dividends, in time saved in the routine work of the current audit, in reviewing the work, particularly, in obtaining a telescopic view of it, in building up goodwill with the client who is apt to regard with favor an assistant, new to the audit, who will not have to ask so many questions, because by referring to his permanent file he can find the answers.